2003
DOI: 10.1080/10575630290034302
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Constituents of Capparis Spinosa of Jordanian Origin

Abstract: Investigation of Capparis spinosa of Jordanian origin lead to isolation of two new compounds beta-sitosterylglucoside-6'-octadecanoate (1) and 3-methyl-2-butenyl-beta-glucoside (2). Linked Scan MS measurements were used to propose a mass fragmentation pattern for the alkaloid Cadabicine isolated here for the second time from nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Its ESI-MS contained an additional peak m/z 267, corresponding to the fatty acyl residue. The 1 H-and 13 C-NMR spectra of 4 were similar to those of octadecanoate and β-sitosteryl glucoside (Khanfar et al, 2003). The 1 H-NMR spectrum of 4 showed a huge peak at 1.2-1.3 ppm corresponding to the fatty acid chain protons.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Its ESI-MS contained an additional peak m/z 267, corresponding to the fatty acyl residue. The 1 H-and 13 C-NMR spectra of 4 were similar to those of octadecanoate and β-sitosteryl glucoside (Khanfar et al, 2003). The 1 H-NMR spectrum of 4 showed a huge peak at 1.2-1.3 ppm corresponding to the fatty acid chain protons.…”
Section: Resultsmentioning
confidence: 66%
“…Alkaline hydrolysis of compound 4 yielded β-sitosterol, glucose, and octadecanoic acid (identified by GC-MS). Collectively, the spectral data indicated that the structure of compound 4 was β-sitosterol-3-O-(6-octadecanoyl) β-D-glucopyranoside (Khanfar et al, 2003).…”
Section: Resultsmentioning
confidence: 97%
“…The presence of alkaloid, such as stachydrine, cadabicine, capparispine, capparispine 26-O-β-d-glucoside, cadabicine 26-O-β-d-glucoside hydrochloride was demonstrated in fruit and roots, but the alkaloid content of C . spinosa root was higher than that of its fruits [14][15][16][17] and quercetin content was higher in fruits than in roots [18]. Indoleglucosinolates such as glucobrassicin, neoglucolorassicin and methoxyglucobrassicin were isolated from roots [19].…”
Section: Discussionmentioning
confidence: 99%
“…In China, C. spinosa has been used since ancient times in traditional medicine especially for the treatment of rheumatism and gout (Fu et al, 2008). With regard to the constituents of the C. spinosa, a number of flavonoids, alkaloids, terpenoids, volatile oils and fatty acids have been reported (Matthäus & Ozcan, 2002;Sharaf et al, 1997;Khanfar et al, 2003;Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%